Hydatidosis, cysticercosis, and tuberculosis rates in bovine slaughtered under state sanitary inspection in Rio Grande do Sul, Brazil - Bica,Roque Fernando Pinheiro (2018)
ABSTRACT This study sought to evaluate the occurrence of lesions suggestive of hydatidosis, cysticercosis, and tuberculosis in animals slaughtered under sanitary inspection of the Divisão de Inspeção de Produtos de Origem Animal (DIPOA), in the state of Rio Grande do Sul. Condemnation data between the years 2009 and 2017 were obtained from Secretaria da Agricultura Pecuária e Irrigação (SEAPI) and presented according to the administrative regions established by SEAPI. In that period, 7,509,544 cattle were slaughtered and condemnations occurred in all regions of the state at varying levels. The mean condemnation values showed the presence of hydatidosis in 523,399 (6.97%), cysticercosis in 92,277 (1.23%), and tuberculosis in 10,595 (0.14%) cattle carcasses. The mean values of hydatidosis diagnoses were higher in the regions of Alegrete (14.19%), Bagé (19.62%), and Pelotas (17.71%). The regions of Osório (1.86%), Santa Maria (2.10%), and São Luiz Gonzaga (1.83%) had highest rates of cysticercosis condemnations. All regions maintained an average bovine tuberculosis diagnosis rate of less than 1% and Estrela region had the highest index (0.70%). Results showed that the three diseases occurred in all regions of the state, the average prevalence rates in each region are variable, and distribution seems to be regionalized. This knowledge contributes to the plans for controlling these diseases, which are zoonoses that cause economic losses to the productive sector.